Nonflammable Polyfluorides-Anchored Quasi-Solid Electrolytes for Ultra-Safe Anode-Free Lithium Pouch Cells without Thermal Runaway - Hu, Anjun (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.